Design of remote incoming supply disconnection system using Radio Frequency (RF) / Samshul Munir Muhamad, Mohammad Nawawi Seroji and Mohd Saleh Shamlani - Muhamad, Samshul Munir; Seroji, Mohammad Nawawi; Shamlani, Mohd Saleh (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
When dealing with unpaid bills, TNB usually ends up to cut OFF the electricity supply to the premise by removing the fuse from the energy meter box. However, this is difficult to be carried out since the meter is sometime inaccessible due to its location, being locked as well as guarded by dogs. This paper proposes a remote system to disconnect the electrical supply via Radio Frequency wave. In this system an additional disconnection device is required to be installed together with the consumer energy meter unit. The transmitter and receiver are equipped with RF module which facilitates one directional communication to perform the disconnection task. The system is also capable to reconnect the supply. It is hoped that the system could reduce the non-payment issues.